(untitled) (Development Service Industry Management, 2023)
The article focuses on issues of formation and implementation of the state policy of managing the development of the tourist complex on the example of the Carpathian region of Ukraine. The purpose of the research is to substantiate the elements of the strategy for the development of the tourist complex of the region. The results of the SWOT analysis of the development of the tourist complex of the Carpathian region of Ukraine are presented. The scenarios (optimistic, pessimistic and pragmatic) of the development of the tourist complex of the Carpathian region of Ukraine are substantiated. The systemic obstacles, purpose and strategic goals of the development strategy of the tourist complex of the Carpathian region of Ukraine were identified. The strategic and operational goals of the strategy for the development of the tourist complex of the Carpathian region of Ukraine and the indicators of their implementation are substantiated. As a result of the identification of potential opportunities, challenges and threats, systemic defects of public management of tourism development in the regions of the Carpathian region of Ukraine, the relevance and advantages of the transition to a joint, unified and coordinated interregional policy in this area have been established and proven. It is about the adoption and implementation of the Strategy for the Development of the Tourist Complex of the Carpathian Region of Ukraine, the goal of which will be the managed, verified development of tourism as a complex, the realization of its potential in the economy, and the increase in the quality of life of the population. It was established that the achievement of the specified goal will be facilitated by the implementation of the following strategic goals: (1) formation and popularization of a joint tourist product; (2) achievement of a unified vision of modernization of the tourist complex of the region; (3) impact on increasing the resource potential of the tourist complex and the regional economy; (4) contribution to the realization of the potential of socio-economic development of territories; (5) smart diversification. It is important to adapt the Strategy toolkit to three possible scenarios: optimistic, pragmatic, pessimistic. In accordance with the specified conceptual provisions, other structural elements of the Strategy were formed, which are operational goals, tasks, implementation mechanisms and tools, financial support, monitoring and control methodology, etc.